Myasthenia Gravis following Low-Osmolality Iodinated Contrast Media. (3rd December 2014) - Bonanni, Luca; Dalla Vestra, Michele; Zancanaro, Andrea; Presotto, Fabio
Abstract : We describe the case of 79-year-old man admitted to our general hospital for a 6-week history of progressive dysphagia to solids and liquids associated with weight loss. To reach a diagnosis a total body CT scan with low-osmolality iodinate contrast agent was performed. Two hours later the patient developed an acute respiratory failure requiring orotracheal intubation and mechanical ventilation. The laboratory and neurological tests allow formulating the diagnosis of myasthenia gravis. In literature, other three case reports have associated myasthenic crisis with exposure to low-osmolality contrast media. This suggests being careful in administering low-osmolality contrast media in myasthenic patients.